Empowering Shepreneurs to achieve the sustainable development goals: Exploring the impact of interest‐free start‐up credit, skill development and ICTs use on entrepreneurial drive. (28th March 2022) - Mazhar, Saman; Sher, Ali; Abbas, Azhar; Ghafoor, Abdul; Lin, Guanghua
Abstract: Recent debates—like agenda 2030—emphasize that women are not just the potential beneficiaries of the sustainable development goals (SDGs), yet they are also active change agents in achieving them. This study used non‐parametric techniques to investigate and compare the impact of three entrepreneur‐supporting interventions—interest‐free start‐up credit, skill‐development short courses, and information and communication technologies (ICTs) use—in lowering the impediments defying women entrepreneurs in Punjab‐Pakistan. We identified 33 barriers and three groups of respondents based on intervention(s) availed. Mean score ranking analysis reveals 25 out of 33 barriers as critical in affecting women entrepreneurs in category one, whereas women entrepreneurs in category two and three are found to face 20 and 14 critical barriers, respectively. Furthermore, we used factor analysis to group these 25 critical barriers into five principal groups: (1) business management & marketing barriers, (2) gender & social barriers, (3) client and customer‐related barriers, (4) public policy and governance barriers, and (5) innovation & knowledge‐management barriers. Moreover, the study advances a comprehensive understanding of underlying grouped barriers to devise coherent plans and collaborative actions—involving local institutions, stakeholders, academia, and industry—for containing these snags and to better harvest the impacts of development initiatives. The study extends the existing literature on techno‐economic disclosure, digital transformation and entrepreneurship, and sustainable knowledge management.